Abnormal liver enzymes in outpatients with eating disorders - Mickley, D. (Yale University School of Medicine, New Haven, CT.); Greenfeld, D; Quinlan, D.M; Roloff, P; Zwas, F (The International journal of eating disorders, 1996)
Objective: This study was undertaken to screen a large series of outpatients with anorexia or bulimia for liver enzyme abnormalities, examining their frequency and their clinical correlates. Method: Eight hundred seventy-nine eating-disordered outpatients presenting at a suburban clinic constituted the subject population. Serum glutamic oxalacetic transaminase, serum glutamic pyruvate transaminase, and gamma glutamyl transpeptidase (SGOT, SGPT, and GGTP, respectively) were drawn at intake. Medical charts were reviewed to obtain further clinical data on all patients with an enzyme elevation. Results: Liver enzymes were abnormally high in 36 patients (4.1%). Elevated SGPT was the most frequent enzyme abnormality and was correlated with lower current and past weight and body mass index (BMI). Discussion: Hepatic dysfunction in eating-disordered outpatients is neither specific nor common. Low weight alone can cause liver damage, yet elevated liver chemistries in patients with anorexia and especially bulima are often not due to their eating disorder